Implementación de la metodología del valor ganado para controlar los costos de una obra conexa en la minera cerro corona, 2017 - Chavez Ruiz, Jonatan Rogelio (2018)
The contractor company Metalarc S.R.L. performs construction projects in the mining company Cerro Corona - Cajamarca. His main problem was the lack of a control tool in the progress of his works, this being the reason why many of his works have not obtained the benefit initially planned. Reason for which it was sought to implement a methodology that allows to control constantly on the costs, being this the Method of the Earned Value. The implementation of this methodology was in the work "Construction of the Solid Waste Warehouse", of 12 weeks’ duration. Where it proceeded to make the budget and schedule, which served as a baseline for subsequent calculations. Then, daily progress data was taken. Then, with these data, the performance indices and cost variations were calculated and estimated every four weeks. Finally, the result in the eighth week was that the final costs would be S /. 20,297.27 more than planned. That is where the decision was made to reduce that amount before reaching week twelve. At the end of the project, the final amount was S /. 15,449.93 on the planned, giving as final result a variation of 3.0% between the planned and the real. The above is beneficial for the company because in the previous works the average variation was 15.0%.